Manokwari Rice Farmers Adaptation: Response to Rice Price Fluctuations - Mikhael, Mikhael; Tapi, Triman; Arfah, Aziza Noor Sheha (Universitas Panji Sakti, 2025)
The rice price fluctuations are a significant challenge for farmers in Indonesia, including in Manokwari, West Papua, which plays a strategic role as a food granary. This research aims to (1) identify the various adaptation strategies of rice farmers in Manokwari Regency in facing rice price fluctuations; (2) analyze internal factors (such as social capital, access to resources, farmer household characteristics); and (3) analyze external factors (such as government policies, institutional support, local market conditions) that influence these adaptation decisions. This research addresses the gap in in-depth studies on specific adaptation dynamics in Manokwari. Using a mixed-methods approach with a sequential exploratory design, qualitative data (in-depth interviews, observations) and quantitative data (questionnaire surveys) were collected from rice farmers in Prafi District. Data were analyzed thematically for qualitative data and using descriptive statistics and logistic regression for quantitative data. The research findings indicate that farmers adopt various adaptation strategies such as income diversification, the use of new technologies, and changes in cultivation practices. Influential external factors include government policies related to prices, market conditions, and institutional support. Significant internal factors include adaptive capacity, social capital, access to resources, as well as literacy levels and trust in others, which proved to be highly significant in strategy adoption. Price fluctuations have a tangible impact on the socio-economic aspects of farmers, pressuring income and welfare. This research concludes that enhancing farmers' adaptive capacity requires holistic interventions that comprehensively address internal and external factors.